Do Macroeconomics Variables Affect Conventional and Islamic Banking Profitability? - Achmad Fadlil Abidillah; Muhamad Nafik Hadi Ryandono (AFEBI Islamic Finance and Economic Review, 2019)
This study aims to examine the impact of external macroeconomic variables on profitability of conventional banking and Islamic banking in Indonesia. Macroeconomic variables included in the model are: inflation, gross domestic product, exchange rate, and money supply. This study took a period of time from 2007 to 2017, quarterly. Using an Engle-Granger cointegration test and error correction model, this study will analyze a short and long term correlation of macroeconomic variables again banking profitability. The results of this study indicate that in short term, conventional bangking’s profitability is influenced by money supply, while in long term is influenced by inflation and currency exchange rates. Then, other results show that macroeconomic variables do not affect Islamic banking’s profitability in the short term, while in long term Islamic banking’s profitability is only influenced by exchange rate of currency. This study provides recommendations to banking management in order to optimizing management of its instruments, so that it can adjust to macroeconomic turmoil in the economy.